2020
DOI: 10.1001/jamapsychiatry.2019.3679
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Autoantibodies Against Neuronal Surface Antigens in Sera of Patients With Psychotic Disorders

Abstract: Patients with antibodies against neuronal surface antigens (NSAbs), including the N-methyl-D-aspartate receptor (NMDAR), typically develop autoimmune encephalitis with characteristic neurological and psychiatric symptoms. 1 In 4% of individuals with NMDAR encephalitis, isolated psychotic episodes occur without simultaneous neurological involvement. 2 This raises the question of whether NSAbs are underdiagnosed in patients with psychotic disorders. Results of studies testing this, however, are contradictory, 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…This has caused considerable interest in investigating a potential role for neuronal antibodies in the pathogenesis of psychiatric syndromes. Various casecontrol studies have produced conflicting results, but a systematic review and meta-analysis found that serum NMDAR antibodies were three times as common in patients with schizophrenia, schizoaffective disorder, bipolar affective disorder or major depressive disorder compared to controls 117,118 . This finding was supported by a more recent large case-control study indicating that serum NMDAR antibodies were more prevalent in patients with first episode psychosis than in the healthy controls, although this was not the case for the other antibodies tested; LGI1, GABA A R and VGKC-complex 119 .…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…This has caused considerable interest in investigating a potential role for neuronal antibodies in the pathogenesis of psychiatric syndromes. Various casecontrol studies have produced conflicting results, but a systematic review and meta-analysis found that serum NMDAR antibodies were three times as common in patients with schizophrenia, schizoaffective disorder, bipolar affective disorder or major depressive disorder compared to controls 117,118 . This finding was supported by a more recent large case-control study indicating that serum NMDAR antibodies were more prevalent in patients with first episode psychosis than in the healthy controls, although this was not the case for the other antibodies tested; LGI1, GABA A R and VGKC-complex 119 .…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…IHC studies: 2.2% of the samples were found positive with 11 novel patterns Plasma samples from 2231 individuals were initially tested by IHC on rat brain tissue, as described 27 . Overall, 106 (4.8%) samples had scores of 1 or higher, of which 56 (2.4%) samples had score 1 (borderline), 42 (1.8%) had score 2 (weak positive), and 8 (0.4%) had score 3 (strong positive) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To test if autoantibodies directly target neuronal surface proteins, rat hippocampal neuronal staining was performed as described previously 27,30 , with small modifications. In brief, neurons were incubated with patients' sera, followed by incubation with anti-human IgG fluorescentlabeled secondary antibody (supplementary Table 1) for 1 h and mounted with mounting medium containing DAPI; all the steps were performed at room temperature.…”
Section: Staining On Live Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat brain sections and primary cell cultures from rat embryo hippocampus were used to detect IgG autoantibodies to neuronal antigens ( 3 ). A strong immunoreactivity of serum antibodies to the middle region of the dentate gyrus and the molecular layer of the cerebellum was identified, with a titer of 1:1,600.…”
Section: Antibody and Antigen Characterizationmentioning
confidence: 99%